Structure and Properties of Polymer Composites and NanocompositesSubjected to Thermomagnetic Treatment - A.D. Stadnick; I.A. Moroz; O.G. Medvedovskaya; V.M. Bilyk (Журнал нано- та електронної фізики)
We have investigated the effect of thermomagnetic treatment on the structure and properties of polymer composites based on bisphenol epoxy resin, polyvinylidene fluoride, polyethylene, poly-4-methylpentene-1. The following powders were used as fillers: electrolytic iron, carbonyl nickel and nanocobalt. The values of the melting and crystallization temperature and also the melting (crystallization) temperature range are determined. The dependence of the degree of crystallinity, the coercive force and residual magnetization of polymer composites on the concentration of filler and the treatment conditions are established.